Estimating multidimensional development resilience - Lee, Seungmin; Abay, Kibrom A.; Barrett, Christopher B.; Hoddinott, John F. (International Food Policy Research Institute, 2024)
Resilience measurement has received substantial attention over the past decade or so. Existing measures, however, relate resilience to a single well-being indicator. This may be problematic in contexts where households face deprivations in multiple dimensions. We explore how sensitive estimates of household-level resilience are to the specific well-being indicator used and show that measures are only weakly correlated across different, reasonable indicators based on expenditure-based poverty, dietary diversity, and livestock asset holdings. We then introduce a multidimensional resilience measure, integrating the probabilistic moment-based resilience measurement approach of Cissé and Barrett (2018) with the multidimensional poverty measurement method of Alkire and Foster (2011). Applying the new method to household panel data, we show that univariate and multidimensional resilience measures can yield varied inferences on the ranking of households as well as potential impact of development interventions.